(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2023)
The study is looking for the optimal configuration of an air-to-water heat pump capable of heating water in a flow-return system. Carbon dioxide is used as a working agent. In the optimization strategy, exergy analysis is considered. Using exergy analysis, the magnitude and the location of any functional or constructive malfunction can be revealed. First, a standard one-stage heat pump system is considered. Due to the high exergy destruction in the throttling valve, the efficiency of the standard system is improved by coupling it with an auxiliary one. The coupling process is undertaken in an internal subcooler-evaporator-heat exchanger. By subcooling the CO2 before entering the throttling valve of the standard cycle, the exergy destruction associated with this process diminishes. To increase the efficiency of the globally coupled system, the heat transferred outside in the gas cooler of the auxiliary heat pump is used in the water heating process. The energetic and exergetic efficiencies of the coupled system increased by 19 % and 18.3 %, respectively, compared to the standard heat pump cycle.